Environment Control to Improve Recombinant Protein Yields in Plants Based on Agrobacterium-Mediated Transient Gene Expression - Fujiuchi, Naomichi; Matoba, Nobuyuki; Matsuda, Ryo (Frontiers in Bioengineering and Biotechnology, 2016)
Agrobacterium-mediated transient expression systems enable plants to produce a wide range of recombinant proteins on a rapid timescale. To achieve economically feasible upstream production and downstream processing, two yield parameters should be considered: (1) recombinant protein content per unit biomass and (2) recombinant protein productivity per unit area–time at the end of the upstream production. Because environmental factors in the upstream production have impacts on these parameters, environment control is important to maximize the recombinant protein yield. In this review, we summarize the effects of pre- and postinoculation environmental factors in the upstream production on the yield parameters and discuss the basic concept of environment control for plant-based transient expression systems. Preinoculation environmental factors associated with planting density, light quality, and nutrient supply affect plant characteristics, such as biomass and morphology, which in turn affect recombinant protein content and productivity. Accordingly, environment control for such plant characteristics has significant implications to achieve a high yield. On the other hand, postinoculation environmental factors, such as temperature, light intensity, and humidity, have been shown to affect recombinant protein content. Considering that recombinant protein production in Agrobacterium-mediated transient expression systems is a result of a series of complex biological events starting from T-DNA transfer from Agrobacterium tumefaciens to protein biosynthesis and accumulation in leaf tissue, we propose that dynamic environment control during the postinoculation process, i.e., changing environmental conditions at an appropriate timing for each event, may be a promising approach to obtain a high yield. Detailed descriptions of plant growth conditions and careful examination of environmental effects will significantly contribute to our knowledge to stably obtain high recombinant protein content and productivity, thus enhancing the utility of plant-based transient expression systems as recombinant protein factories.